2022
DOI: 10.1002/lio2.991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating YouTube videos on sialendoscopy as an educational resource for patients

Abstract: Objectives: Patients are increasingly relying on YouTube for health information. We objectively evaluated the quality and comprehensiveness of sialendoscopy YouTube videos available to patients. We further investigated the relationship between video content and video popularity. Methods:We identified 150 videos using the search term "sialendoscopy." Videos were excluded if they were lectures for medical professionals, operating room (OR) recordings, unrelated, non-English, or non-audio. Video quality and compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Our study found that ChatGPT responses exceeded this grade level recommendation, averaging an FK score of 14.66, a collegiate reading level. Prior studies assessing ChatGPT’s grade level when responding to healthcare-related questions have found similar results [ 8 - 10 ]. Compared to other online sources, ChatGPT’s readability is on par.…”
Section: Discussionsupporting
confidence: 55%
“…Our study found that ChatGPT responses exceeded this grade level recommendation, averaging an FK score of 14.66, a collegiate reading level. Prior studies assessing ChatGPT’s grade level when responding to healthcare-related questions have found similar results [ 8 - 10 ]. Compared to other online sources, ChatGPT’s readability is on par.…”
Section: Discussionsupporting
confidence: 55%
“…Within digital medial there is an assumption that popularity of content correlates to quality and reliability of information. 17,22,23 Our study found no correlation between video quality and popularity. However, videos closer to the top of the YouTube search position had a positive correlation with our NI score.…”
Section: Discussionmentioning
confidence: 56%
“…Although we found audio-visual quality to have significant correlation, prior studies found a variety of results ranging from positive correlation to no correlation. [17][18][19] Video duration was also associated with more accurate and reliable YouTube videos. We found that longer videos included more content, and therefore were able to score higher on the information quality metrics that were implemented in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, two-thirds of TURP videos in our analysis were produced in 2021–2022. However, such online resources are generally not curated by medical experts, so whether viewers are learning correct medical techniques and principles is unclear ( 16 - 22 ). Here we performed what appears to be the first assessment of the educational quality of TURP videos on YouTube, for which we custom-designed a quality checklist.…”
Section: Discussionmentioning
confidence: 99%